"Humane" Immigration Enforcement and Latina Immigrants in the Detention Complex. (July 2017) - Gómez Cervantes, Andrea; Menjívar, Cecilia; Staples, William G.
We explore the criminalization of Latina immigrants through the interwoven network of social control created by law, the justice system, and private corporations—the immigration industrial complex. Considerable scholarly research has focused on understanding the overtly coercive practices of deportation and the consequences for families and communities; less attention has been devoted to the social control mechanisms of detention facilities and "Alternative to Detention Programs" (ATD programs) operating in the United States. We know relatively little about the consequences for immigrant populations, especially of the purported "humane" practices in the enforcement apparatus. Based on existing documents produced by governmental offices, including Department of Homeland Security, Immigration and Customs Enforcement, Border Patrol, Government Accountability Office, nonprofit organizations, advocacy groups, and private correctional facilities, we conducted semistructured interviews with 11 immigration lawyers who have access to women who are and/or have been detained, are in supervised ATD programs, are/were in deportation proceedings, or attempt(ed) to claim asylum. An examination of immigration confinement, especially the laws and policy decisions behind the exponential increase in these detentions, reveals important gender dynamics in these practices. The subtle and benevolence-signaling discourse evoking "family, " "motherhood, " and the care of children masks the harsh "business as usual" tactics that treat women and their children in ways indistinguishable from those used in the criminal justice system. We contend that this feminized and infantilized language functions to conceal widespread civil and human rights violations, physical and sexual violence, and mistreatment reproduced by the immigration detention system today.